Differences in The Effects of Coconut Oil and Aloe Vera in Accelerating The Healing of Diaper Rashes in Babies - Yanti, Dian Anggri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Baby's skin tends to become easily irritated due to low humidity. Irritation can occur in babies due to environmental temperatures that are too cold so that the baby's skin easily dries out and becomes itchy. Diaper rash is an inflammatory condition of the skin on the baby's thighs and buttocks due to friction between the skin and diapers which generally contain the baby's feces and urine for a long time. Diaper rash has signs of swelling and reddish skin on the thighs and buttocks. To treat diaper rash, non-pharmacological therapy is needed, such as administering coconut oil or aloe vera, which are known to contain many properties such as proteins, carbohydrates, vitamins and secondary metabolites which can act as antibacterials and antiseptics. The type of research chosen was quantitative with a pre-experimental design using the two group pretest-posttest method. The samples were babies aged at least 3 months and a maximum of 1 year who were known to have diaper rash which was determined using the purposive sampling method. The sample of babies consisted of 18 people, which would be divided into 9 people for the two types of interventions carried out. The instruments used are an observation sheet for the degree of diaper rash and SOP, where the results will be analyzed using univariate and bivariate. The results of the study showed that the administration of coconut oil and aloe vera could influence the diaper rash category, where there was a decrease in the mean score on the post-test of 3.22 and 3.11 respectively. The results of the sample paired t-test analysis show that the p-value is 0.000, which means there is a significant difference in the effect between giving coconut oil and aloe vera in accelerating the healing of diaper rash in babies.